On Strong Convergence Theorems for END Sequences (Journal of Mathematical Study, 2017)
In this paper, we study the strong law of large numbers for a sequence ofEND random variables. Our results extend the corresponding ones for independentrandom variables and negatively orthant dependent (NOD, in short) random variables.